Jak powstały nowe nazwy ulic w powojennej Zielonej Górze? - Żuraszek-Ryś, Iwona (Wydawnictwo „Poznańskie Studia Polonistyczne" i Wydawnictwo Poznańskiego Towarzystwa Przyjaciół Nauk, 2012)
This is a follow-up article to the earlier article Post-war street names in Zielona Góra that relates to the ways former German urbanonyms were incorporated into the Polish linguistic system. The present article focuses, however, only on those forms that do not refer to earlier names in any way, that is, on completely new names. The material presented in the article includes a hundred urban place names (excerpted from a document, or more precisely from a five-page typescript with no date and no signature in which German names of streets of the town are accommpanied with their Polish counterparts). The comprehensive survey of these forms provides a conclusion that the Polonization of urbanonyms was not by all means an easy task to perform, and that the people responsible for its implementation had to face and come to grips with different problems of linguistic and non-linguistic nature. Things as they were, however, make us realise today that some of the solutions can raise our objection and reservation on the matter.
Keywords: urbanonyms; appelatives (common words); motivation; anthroponyms; Polonization